Potent Analogues of Abscisic Acid – Identifying Cyano‐Cyclopropyl Moieties as Promising Replacements for the Cyclohexenone Headgroup. Issue 12 (24th March 2018) - Frackenpohl, Jens; Bojack, Guido; Baltz, Rachel; Bickers, Udo; Busch, Marco; Dittgen, Jan; Franke, Jana; Freigang, Jörg; Grill, Erwin; Gonzalez, Susana; Helmke, Hendrik; Hills, Martin J.; et al.
Abstract : Synthetic analogues of plant hormone abscisic acid (ABA) bearing a yet unexplored head group motif were prepared based on a combination of agrochemical experience, in vivo hits and structure‐based design. It could thus be explored how modifying key parts of ABA's cyclohexenone unit influenced receptor affinity and in vivo efficacy against drought stress in selected crops. Cyano‐cyclopropyl groups proved to be suitable replacements of the cyclohexanone moiety leading to ABA analogues with strong activity in vitro and in vivo. Their efficient and versatile synthesis proceeded via Stille or Sonogashira couplings as the key steps. Combining novel cyano‐cyclopropyl headgroups with previously identified substituents in the terpenoid side chain afforded the most promising effects against drought stress in crops, particularly canola and wheat. Abstract : A novel headgroup bearing a cyano cyclopropyl moiety has been identified as a key motif, which proved to be a suitable replacement of ABA's cyclohexenone unit. These findings gave rise to a series of novel ABA analogues with strong efficacy in vivo against drought stress in several crops.